Selecting A Digitization Device for Bone Marrow Aspirate Smears - Kock, Farina; Pontones, Martina; Ghete, Tabita; Metzler, Markus; Höfener, Henning (Laboratory Investigation, 2025)
The digitization of histologic specimens has become increasingly common within the last years; however, digitization of cytologic slides has its own challenges and there is little guidance on the optimal use of digitization devices for cytopathology. For the morphologic analysis of cells in, for example, bone marrow aspirate smears, different studies have used a variety of scanner setups and there is no direct comparison between those. This makes it nontrivial to choose an optimal scanner setup. This work pragmatically analyzes different whole-slide image scanners but also cost-effective light microscope solutions and identifies important aspects for the digitization of cytopathological samples. We aimed to share our experience in selecting a digitization device for generating a bone marrow aspirate data set.
CRIS-Team Scopus Importer:2025-03-28
Keywords: bone marrow aspirate smear; cytology; digitization; light microscope; whole-slide image scanner